MONOCYTE SUBSETS IN HEALTHY ADULTS AND SEPSIS PATIENTS - A. A. Kalashnikova; T. M. Voroshilova; L. V. Chinenova; N. I. Davydova; N. M. Kalinina (Медицинская иммунология, 2018)
Monocytes play a key role in the development of immune response in bacterial infection, because of their phagocytic, antigen-presenting and secretory functions. There are three subpopulations of monocytes: “classical” CD14+CD16-, “intermediate” CD14+CD16+, and “nonclassical” CD14+dimCD16+. These monocyte subtypes have different phenotypes and functions. The ratio of appropriate subpopulations varies with development of the antibacterial response. The aim of the present research was to study phenotypes of the monocyte subpopulations in the patients with sepsis, and changes in the monocyte subpopulation ratio, depending on the presence of bacteria in circulating blood of the patients, as well as to estimate contribution of the monocyte subpopulations to the cytokine production. We observed 16 patients with sepsis (10 men and 6 women; mean age, 58±14 years, SOFA 9.4±2.1; a total of 44 blood samples) examined in dynamics. The control group included healthy adults (n = 23, 12 men and 11 women; mean age, 51±13 years). Laboratory studies included bacteriological cultures, determination of absolute and relative numbers of subpopulations of classical, intermediate and non-classical monocytes and their expression of HLA-DR and CD64, determination of IL-6, TNFα, IL-1β, IL-10 concentration in blood serum. Absolute number of monocytes was increased in the sepsis patients, the ratio of classical monocytes was also increased, like as relative and absolute numbers of  intermediate cells. Meanwhile, the subpopulation of non-classical monocytes did not change significantly. The monocyte subpopulation ratio depended on the presence of bacteria in blood, i.e., a higher proportion of intermediate cells was observed in the samples positive for bacteria in blood cultures. The ratio of subpopulations was restored after elimination of bacteria from the circulation. The expression density of LPS receptor (CD14), IgG receptors (CD16 and  CD64) was found to be increased, especially in the subpopulations of intermediate and nonclassical monocytes. In all subpopulations of monocytes, expression of HLA-DR is reduced, most notably in classical monocytes, least in intermediate cells. There was a significant increase in serum levels of IL-6, IL-1β, TNFα and IL-10 cytokines. Direct correlation between the absolute number of classical monocytes and IL-6 concentration was revealed, as well as intensity of multiple organ dysfunction. Increase in absolute amount of classical monocytes and IL-6 concentration might serve as an indirect criterion for evaluation of endothelial activation, an active producer of IL-6 and myeloid cell growth factors. A direct correlation between the percentage of CD14+CD16+ cells and IL-10 concentration in blood serum indicates to an important role of intermediate monocytes in IL-10 production. IL-10 suppresses the antigen-presenting function of intermediate cells, namely, expression of HLA-DR molecules, as suggested by inverse correlation between the IL-10 concentration and HLA-DR expression density on CD14+CD16+ cells. We have also determined an inverse correlation between the degree of multi-organ dysfunction  and relative amount of HLA-DR+ monocytes. The larger was a classical monocyte subpopulation, the more noticeable was a decrease of this index. The studies in ratios of monocyte subpopulations help to understand the mechanisms of antibacterial protection in sepsis. Monitoring of classical monocyte numbers and serum concentrations of IL-6 is necessary for a comprehensive assessment of inflammatory response in sepsis. Determination of HLADR expression on monocytes allows us to evaluate the intensity of immune suppression in critically ill patients.